2010
DOI: 10.1166/jnn.2010.2403
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Urine Crystallites and Its Influencing Factors by Nanoparticle Size Analyzer

Abstract: The difference of urine crystallites under 1000 nm in 10 patients with urolithiasis and 10 healthy subjects with no history of urolithiasis was comparatively studied with the nanoparticle size analyzer. By comparing the differences of intensity-autocorrelation curve, polydispersity index (PDI), Zeta potential, and relative error of average diameter of the two kinds of urine crystallites, it was concluded that the urine crystallites of healthy subjects were more stable than those of patients. The urine crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…A smaller particle corresponds to a faster Brownian movement, leading to a faster scattering intensity change and an inferior signal correlation as well as quick variations in the attenuation of curves. [22][23][24] A faster attenuation of the autocorrelation curve corresponds to a steeper curve and shorter decay time. By contrast, larger particles correspond to slower Brownian movement, leading to a slower scattering intensity change and corresponding in turn, to better signal correlations and slower attenuation of the autocorrelation curve.…”
Section: Intensity-autocorrelation Curve Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…A smaller particle corresponds to a faster Brownian movement, leading to a faster scattering intensity change and an inferior signal correlation as well as quick variations in the attenuation of curves. [22][23][24] A faster attenuation of the autocorrelation curve corresponds to a steeper curve and shorter decay time. By contrast, larger particles correspond to slower Brownian movement, leading to a slower scattering intensity change and corresponding in turn, to better signal correlations and slower attenuation of the autocorrelation curve.…”
Section: Intensity-autocorrelation Curve Changesmentioning
confidence: 99%
“…[1][2][3] Therefore, the crystallites in urine are crucial factors affecting the formation of uroliths. [4][5][6] Previous studies 5,6 have found differences between the urinary crystallites (,1000 nm in size) of patients with urolithiasis and healthy subjects without any urolithiasis history. These studies concluded that the morphology, particle size, aggregation, and crystal phase of nanocrystallites in the urine of lithogenic patients remarkably differ from those of healthy persons.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, the current research on adhesion between renal tubular epithelial cells and crystals mainly focuses on micron grade COM and COD crystals. 6,11 Only a few studies about nanocrystals in urine are available, 12,13 and the interaction between renal tubular epithelial cells and CaOxa crystals with a size of less than 200 nm has yet to be reported. In fact, numerous submicron microcrystals exist in urine, and these microcrystals are the basis for the formation of micron grade crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The nanocrystals observed (i.e., 100-300 nm) were consistent with another study that reported urinary crystallites from healthy subjects ranging from 100 to 350 nm in size. 55 A large proportion of crystals we observed were larger than urinary exosomes, which range from 20 to 100 nm. 56,57 To ensure optimal measurements, we used a consistent camera level, detection threshold, focus, and flow rate, as each of these parameters could affect particle assessment.…”
Section: Discussionmentioning
confidence: 73%